Analysis of entrance region flow of Bingham nanofluid in concentric annuli with rotating inner cylinder. (20th November 2019) - Venthan, Selvam Mullai; Amalraj, Isaac Jayakaran; Kumar, Ponnusamy Senthil
Abstract : This work analyses the entrance region flow of Bingham nanofluids in cylindrical concentric annuli. In this discussion, water is used as the base fluid which is embedded with the silver(Ag) and copper(Cu) nanoparticles coalescing with Bingham fluid. The investigation has been carried out by rotating the inner cylinder, while the outer cylinder is assumed to be at rest. A finite‐difference analysis is used to obtain the axial, radial, tangential velocity components and the pressure along the radial direction. With the Prandtl's boundary layer assumptions, the continuity and momentum equations are solved iteratively using a finite difference method. Computational results are obtained for various non‐Newtonian flow parameters, different volume fraction parameters and geometrical considerations. This work's main interest is to study the development of velocity profiles and pressure drop in the entrance region of the annuli. The present results are compared with the results available in the literature for various particular cases and it is found to be in good agreement.